2015
DOI: 10.1371/journal.pone.0136063
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Cryptic Parasitoid Diversity in Horismenus (Chalcidoidea, Eulophidae)

Abstract: Horismenus parasitoids are an abundant and understudied group of eulophid wasps found mainly in the New World. Recent surveys based on morphological analyses in Costa Rica have quadrupled the number of named taxa, with more than 400 species described so far. This recent revision suggests that there is still a vast number of unknown species to be identified. As Horismenus wasps have been widely described as parasitoids of insect pests associated with crop plants, it is of high importance to properly establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…The molecular analyses of the diversity within the four Chalcidoidea genera studied showed discrepancies with the morphological analysis. This finding is in line with previous studies on hymenopteran parasitoids [ 23 , 43 , 44 ]. For example, Mottern and Heraty [ 45 ] found that one species of the parasitoid previously described as Cales noacki were actually ten different Cales species.…”
Section: Discussionsupporting
confidence: 93%
“…The molecular analyses of the diversity within the four Chalcidoidea genera studied showed discrepancies with the morphological analysis. This finding is in line with previous studies on hymenopteran parasitoids [ 23 , 43 , 44 ]. For example, Mottern and Heraty [ 45 ] found that one species of the parasitoid previously described as Cales noacki were actually ten different Cales species.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, these findings have important evolutionary and applied implications. Divergent selective factors that act on the plants and insects associated with wild and cultivated bean populations can lead to specialization and in extreme cases genetic differentiation and host race formation (Alvarez et al, 2007;Laurin-Lemay et al, 2013;Kenyon et al, 2015). There is further evidence for our bruchid-bean system that shows that bean domestication has selected for different behaviors in host use, not only in seed beetles, but also in the natural enemies of these beetles (Benrey et al, 1998;Campan and Benrey, 2004;Aebi et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…We followed the recommendations by Zhang et al (2013) and integrated the bPTP model with their evolutionary placement algorithm (EPA) to count the number of OTUs on the phylogeny (bPTP-EPA). This method was previously successfully applied to several organismal groups (e.g., Kenyon et al, 2015;Morard et al, 2016;Nieto-Montes de Oca et al, 2017). The analysis was conducted using the portal provided by the authors (http://species.h-its.org/ptp/) based on the default parameters.…”
Section: Species Delimitation and Biogeographical Inferencesmentioning
confidence: 99%